2012
DOI: 10.1089/jamp.2012.1su4
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of Techniques for Using Planar (2D) Imaging for Aerosol Deposition Assessment of Orally Inhaled Products

Abstract: Two-dimensional (2D or planar) imaging with (99m)Tc radiolabels enables quantification of whole-lung and regional lung depositions for orally inhaled drug products. This article recommends standardized methodology for 2D imaging studies. Simultaneous anterior and posterior imaging with a dual-headed gamma camera is preferred, but imaging with a single-headed gamma camera is also acceptable. Correction of raw data for the effects of gamma ray attenuation is considered essential for accurate quantification, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 54 publications
3
76
0
2
Order By: Relevance
“…32 The choice of regions of interest was discussed in a recent recommendation. 24 Our results confirm that the Akita device offers a better method for drug administration to the peripheral lung compared with other modalities of nebulization, but they suggest that it is the device itself rather than the settings that are supposed to target differentially central or peripheral airways. Indeed, the bolus of air after drug delivery did not improve the deposition in this region, similar to the central targeted nebulization.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…32 The choice of regions of interest was discussed in a recent recommendation. 24 Our results confirm that the Akita device offers a better method for drug administration to the peripheral lung compared with other modalities of nebulization, but they suggest that it is the device itself rather than the settings that are supposed to target differentially central or peripheral airways. Indeed, the bolus of air after drug delivery did not improve the deposition in this region, similar to the central targeted nebulization.…”
Section: Discussionsupporting
confidence: 70%
“…24 Images were acquired using a 128 ϫ 128 matrix for 1 or 2 min for the device (including the nebulizer and filter) and airways, respectively. The spatial resolution of this system is 5.3 mm at 10 cm.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…(67,68) In the previous validation study of Tian et al, (61) acceptable agreement was found between the in vivo results of Newman et al (62) and CFD computed airway predictions transferred to 2D planar images for the Novolizer inhaler, which was considered only at the PIFR of 99 LPM (fast inhalation), as well as a softmist inhaler also considered at a single flow rate. The methods established in the previous study of Tian et al (61) are repeated in the current study to evaluate the more challenging scenario of a single DPI evaluated at multiple flow rates generating different aerosol size distributions and tested in two separate airway geometries.…”
Section: Selection Of the In Vivo Dataset And Inhalation Waveformmentioning
confidence: 79%
“…As described, the method used to segment the 2D planar image can influence the predictions of regional lung deposition, (67) and a newly recommend method for dividing planar images was described (68) after the publication of Newman et al (62) However, for validation purposes, the goal was to match the techniques used in the selected in vivo experiments as closely as possible. For the purpose of comparison, acceptable agreement between the CFD predictions and in vivo data will be determined based on the average relative error evaluated in the three regions of interest ( MT, C, and I+P) having a value of 15% or less.…”
Section: Deposition Fraction Calculations and Mappingmentioning
confidence: 99%